Chemical Control of Wild Sorghum [Sorghum arundinaceum(Del.) Stapf.] in Faba Bean (Vicia faba L.) in the Northern State of Sudan (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted at Merowe Research Stationfarm, in the Northern State, Sudan, during 2008/2009 and 2009/2010seasons. The objectives of the experiment were to determine the damageinflicted by a wild sorghum species (Sorghum arundinaceum (Del.)Stapf.) on the yield of faba bean (Vicia faba L.) and to evaluate theefficacy of the post-emergence herbicide clodinafop-propargyl (Topik) onwild sorghum and its effect on faba bean yield. The wild sorghumreduced faba bean crop stand and straw and seed yields by 53% -76%,76% -79% and 88% - 91%, respectively, compared with the hand-weededcontrol. Faba bean was tolerant to the herbicide. The herbicide, at allrates, effected complete (100%) and persistent control of the wildsorghum and resulted in faba bean seed yield comparable to the hand-weeded control. The lowest dose (0.075 kg a.i./ha) of the herbicide usedwas equal to 75% of the dose recommended for the control of wildsorghum in wheat. It is concluded that clodinafop-propargyl at 0.075 kga.i./ha could be used in controlling wild sorghum in faba bean. At thisrate, the marginal rate of return was about 35 which indicating that everymonetary unit (SDG 1) invested in the mentioned treatment would bereturned back, plus additional amount of 35 SDG.